MEMPERKOKOH KUALITAS PENDIDIKAN MADRASAH BERBASIS MANAJEMEN MUTU TERPADU (TQM) - Ali Murtadho (IAIN Pekalongan, 2012)
The upgrading of quality is one of the prerequisites hence we are able to come into an era of globalization which is filled with competition. The existence of madrasahas Islamic educational institutions will not be separated from global competition. For that the improvement of quality is a major agenda in improving the quality of madrasahin order to survive in the global era. TQM (Total Quality Management) is the concept of an integrated quality improvement in management and is still fairly new in the world of education. This article attempts to implement TQM concepts to madrasah. Although the existence of a formal madrasahis same to schools, the uniqueness of Islamic culture still distinguishes the general school culture. TQM Implementation is expected to improve the quality of madrasah.